We Do Not Want Any More Hippies: Legality Criteria, Moralities, and Access Disputes to Habitats in an Urban Expansion Zone - Oriolani, Federico Agustín (2025)
Since the COVID-19 pandemic, complaints of usurpations have increased on Mar del Plata’s South Coastal Promenade. Many cases reported by residents involve self-construction of houses by young people from middle-class backgrounds, using bio-construction practices. This article explores the assessments of long-term residents who oppose the newcomers, the legal definitions and criteria at stake, and the practices that emerge in the name of the law. Based on fieldwork framed within a qualitative perspective, I reconstruct the practices and arguments of the actors through in-depth interviews and participant observation. I show that the controversies over the use of the category “usurpation”, the opposition to these housing projects by neighbors —and not by people claiming ownership— and the procedures to prevent their success, introduce a series of territorial tensions and disputes where the deployment of the Law as a parameter for regulating the possibilities of settling in a neighborhood is used arbitrarily and unequally by those who consider themselves acting under normative criteria.